"Forming Partnerships": Extramarital Songs and the Promotion of China's 1950 Marriage Law. (26th December 2017) - Gibbs, Levi S.
Abstract: Shortly after a push to promote China's 1950 Marriage Law in 1953, scholars from the Chinese Music Research Institute on a collection trip to a small locality in northern China encountered a large number of folksongs about extramarital affairs. They interpreted this as evidence of the need for marriage reform. The folksong lyrics highlighted controversial aspects of the Marriage Law by espousing one of the law's central tenets – free love – while also expressing women's desires to leave their husbands. In this article, I explore how the researchers placed the song lyrics in a liminal moral-temporal category between "feudal" arranged marriage and the new marriage system before declaring the songs to be relics of the victimization of women in a "feudal" past. I argue that additional light-hearted elements complicate the researchers' conclusion and suggest that when the promotion of social agendas in the 1940s and 1950s cast songs about illicit affairs as morally ambiguous, Chinese scholars chose to ascribe the songs' "roots" to other groups or to the "feudal" past of the people they sought to praise and/or transform. 摘要: 在 1953 年贯彻 1950 年《中华人民共和国婚姻法》的过程中，一批来自中央音乐学院中国音乐研究所的研究员到山西省河曲县搜集民歌时，遇到了大量关于婚外情的民间歌曲而将其解释为需要婚姻改革的证据。搜集的歌词突出了《婚姻法》的有争议的方面，拥护了《婚姻法》的中心原则之一：自由恋爱，可也同时表达了女性离开丈夫的愿望。本篇文章探讨研究人员如何将歌词放在"封建"婚姻与新婚姻制度之间的阈限道德时空类别中，然后才声称歌曲是妇女在过去的"封建"时代深受伤害的遗留物。作者认为歌词当中附加的幽默元素使研究人员的结论复杂化，并且表明，当 20 世纪 40 年代和 50 年代促进社会变革的议程使得关于"打伙计"的民歌被型塑为道德上模棱两可的时候，当时的中国学者选择将民歌之"根"归于本地老百姓"封建"的过去或者归于其他群体的影响，而这些老百姓是他们旨在歌颂和/或变革的。